Tour Guiding Practice: English Speaking Learning Phenomenon for Tour & Travel Students - Rachman, Arief F.; Hutagalung, M. Husen; Mukminin, Amirul (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Tour guiding is an essential subject for Tour & Travel students at Trisakti Institute of Tourism, Jakarta. The subject is a practical credit class where students will act as a guide and deliver information in two-way communication in English during the trip. Aim of the paper is to study the English learning phenomenon during practical class subject of tour guiding. It used a qualitative method to explore English learning process during tour guiding, and it is analyzed by Interpretative Phenomenology Analysis (IPA). Findings show that English learning in tour guiding practice applied to opportunity to practice English speaking in tour guiding, assignments as tour guide on the itinerary, and internalization to mindset. Keywords: tour guide, opportunity to practice, assignments, internalization to mindset, interpretative phenomenology analysis, out of town tour